Impact of Demonetization on Indian Citizens - Soni, Shriprakash; Karande, Vinit (International Research Journal of Management, IT & Social Sciences, 2017)
Paper currency i.e. currency note is basically a promissory note that simply recommends that the payee has promised to pay that amount to the payer. The same is written on every currency paper as well. This is authenticated in India by the RBI Governor. This currency notes people can you for the exchange of goods and services. It is considered as a legal tender for performing transactions. Demonetization means the scrapping of old currency notes and cancelling their legal status of tender. Shri Narendra Modi, The Indian Prime Minister, in his speech to the nation on 8th November, 2016 declared the demonetization of the Indian currency notes Rs. 1000 and Rs. 500 with effect midnight of 8th November, 2016. This move sent the whole country in a wobbly. The Honble Prime Minister specified this decision is a decisive attack against the black money being stored by the citizens of the country as well as a step to counter terrorism which was being funded by counterfeit money. This decision cancelled the legal status of the high value currency notes of INR 500 and 1000 with immediate effect and introduced new Rs. 2000 and Rs. 500 notes. This is really an unexpected surprise for all Indians. This sudden decision affected the several sectors including the Indian economy. Positive and negative impacts of the demonetization decision on Indian citizens are covered in this paper with the help of primary and secondary data. This paper is a sincere attempt to study the present scenario, short term and long term effects of demonetization in India.